Cultural Value Factors That Affect Mother and Child Health - Inang Winarso; Ressa Ria Lestari (Yayasan Jurnal Perempuan, 2019)
Mother and child health as a key indicator of community welfare is measured by the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). But why have efforts to reduce MMR and IMR not yet reached the target? This research answers this question by using an approach of cultural values in mother and child health. The focus of this research is on the human life cycle starting from marriage, pregnancy, birth and death in Situbondo Regency, East Java and Ngada Regency, NTT. Research has found four cultural elements that predominantly influence health beliefs, family and community decisions in dealing with maternal and infant health problems. These cultural elements are the religious system, the kinship system, the knowledge system and the livelihood system. These four systems can increase or decrease the risk of maternal and infant mortality. The government must consider the cultural values of the community in making health policies. First, strengthen factors that reduce the risk of maternal and child mortality. Second, reduce the factors that increase the risk of maternal and child mortality.